2015
DOI: 10.1620/tjem.236.107
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dysmenorrhea and Its Correlating Lifestyle Factors in Japanese Female Junior High School Students

Abstract: Dysmenorrhea is a common menstrual disorder experienced by adolescents, and its major symptoms, including pain, adversely affect daily life and school performance. However, little epidemiologic evidence on dysmenorrhea in Japanese adolescents exists. This cross-sectional study aimed to determine the prevalence of and identify factors associated with dysmenorrhea in Japanese female junior high school students. Among 1,167 girls aged between 12 and 15 years, 1,018 participants completed a questionnaire that soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
67
3
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(89 citation statements)
references
References 27 publications
12
67
3
7
Order By: Relevance
“…The prevalence in guidance and high school students was less than university students, which was comparable to the studies reported by Kazama et al (2015) and Agarwal and Venkat (2009). In these studies, the prevalence of dysmenorrhea increased with age (49,50).…”
Section: Discussionsupporting
confidence: 81%
“…The prevalence in guidance and high school students was less than university students, which was comparable to the studies reported by Kazama et al (2015) and Agarwal and Venkat (2009). In these studies, the prevalence of dysmenorrhea increased with age (49,50).…”
Section: Discussionsupporting
confidence: 81%
“…The possible reasons for the discrepancy among the estimates could be the difference in the life style of study subjects, the difference in use of selected age group, difference in perception of pain during menstruation, the absence of universally accepted technique of defining dysmenorrhea, a probable disparity in the methods of data collection, study definitions of dysmenorrhea and pain. But our study was consistent with studies done in Japanese Female Junior High School Students and other studies as mentioned by Kazama et al [12], Unsal et al [19], Kumbhar et al [23] and Charu et al [25].…”
Section: Discussionsupporting
confidence: 93%
“…The Chisquare analysis also showed that dysmenorrhea is responsible for significant absenteeism from class (X 2 =15; df=2; p=0.001), loss of concentration (X 2 =12.85; df=2; p=0.02), lack of focus on exam (X 2 =7.4; df=2; p=0.025). Different studies agree with our study findings [9,[12][13][14]17,18,[21][22][23][24]. The negative effect of dysmenorrhea comes at its peak when it brings about missed exams and absenteeism.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations